Oracle 11i E-Business Suite from the Front Lines - J Wells, April (CRC Press, 2009)
* Introduces the new 11i suite of products and their features * the responsibilities of the Apps DBA versus that of the typical Oracle DBA * Provides an overview of the inner workings of the Apache server * Describes how Oracle uses Java and Java components and the effect on system administration * Enables setup and troubleshooting of printing within 11i * Addresses how to maximize the efficiency of system patching * Explores cloning, alternative methods, and clone breakage and response * Reviews ways to create a batch processing environment through concurrent processing * Highlights the features of AutoConfig and Oracle Application Manager